Impact of land use and land use history on fruits production of Vitellaria paradoxa (Shea tree) according to agroclimatic zones in Mali (West Africa) - Kelly, Bokary Allaye; Poudyal, Mahesh; Bouvet, Jean-Marc (Current Botany, 2019)
To understand how various factors influence phenological patterns like fruit production and the extent of phenological variability as survival strategy in different environments, fruit production of shea trees was studied in different agroclimatic zones (North Sudanian, South Sudanian and North Guinean) in Mali. Three sites were selected for this study and in each site; two stands (field and fallow) were concerned. For each stand, three “land use history or land management" i.e. new fields/fallows (1-5 years), medium (6-10 years) and old (10 years) were considered and permanent plots of 0.25 ha were established. 60 adult shea trees (DBH) ? 10 cm) were selected by site and monitored for fruit production assessment. The nested analysis of variance on the yield showed a significant site effect and significant effect of land use history within stand. However, stand effect within site was not significant. Factors like site and land management (land use history) appear to be determinant for fruit production of V. paradoxa. The site of Mperesso in the South Sudanian zone showed the highest fruit mean yield (11 kg/tree), significantly higher than the fruit mean yield observed at Daelan (7 kg/tree) in the North Sudanian zone and that observed at Nafégué (6 kg/tree) in the North Guinean zone. For field stand, old fields showed highest mean yield in all sites. For fallow stand, old fallows showed the lowest mean yield in most of cases. Different pattern was observed between field and fallow stands regarding the effect of land management. More fields are aged, more they influence positively fruit production whereas more fallows are aged, and more they influence negatively fruit production. This study highlighted the importance of land management practices and therefore, any domestication program to be successful should consider the potential effect of management practices.